Effect of different preceding crops and land preparation methods on the agrophysiological and health parameters of Hevea brasiliensis Muell. Arg clone GT 1 in southwestern Côte d'Ivoire - Ballo Esperence Kouadio; Soumahin Eric Francis; Ballo Koffi Celestin; Elabo Agnyman Eliathe Angeline; Adou Bini Yao Christophe; Kouadio Yatty Justin; Obouayeba Samuel (European Scientific Journal, ESJ, 2018)
Land preparation method and preceding crops affect the evolution of rubber trees. Its ignorance and/or poor execution do not allow the efficient development of the agronomic and economic potentialities of plantations. In order to remove this constraint, a study was undertaken in southwestern Côte d'Ivoire. The rubber trees were planted at 510 trees/ha according to a Fisherblock experimental design, of six preceding crop treatments with three repetitions. Only one latex harvesting system was applied (S/2 d/4 6d/7 ET 2.5% Pa 1 (1) 6/y). The parameters measured were rubber yield, annual average girth increment, physiological profile, sensitivity to tapping panel dryness and sensitivity to root rot caused by the genus Fomes. The results showed that the rate of rubber trees found in the plots was good (90.73± 0.47 %) and had varied with land preparation method depending on the preceding crops. Vegetative growth at tapping (2.05±1.36 cm.year -1 ), and average rubber yield (2053±179 kg.ha-1 .year -1 ) and the rate of tree loss due to the genus Fomes (8.33±0.42%) were influenced by land preparation method. The good productivity, the good physiological state of the rubber trees were characterized by a well balanced physiological profile and a tapping panel dryness rate (3.60 ± 1.74%), independently of treatments. The Agroeconomic results showed that mechanically prepared fallow (813641 FCFA.ha-1 .year -1 ) was the best preceding crop and land preparation method. This technical result has two main interests for the national rubber-growing industry, since it actively participates in the national policy for fighting against deforestation but also contributes to the establishment of a secondary forest by the attributes of the rubber-growing plant cover.